Antibacterial activity of fractions from three Chumash medicinal plant extracts and in vitro inhibition of the enzyme enoyl reductase by the flavonoid jaceosidin. Issue 6 (19th March 2017) - Allison, Brittany J.; Allenby, Mark C.; Bryant, Shane S.; Min, Jae Eun; Hieromnimon, Mark; Joyner, P. Matthew
Abstract: We have investigated the in vitro antibacterial bioactivity of dichloromethane-soluble fractions of Artemisia californica, Trichostema lanatum, Salvia apiana, Sambucus nigra ssp. cerulea and Quercus agrifolia Née against a Δ tolC mutant strain of Escherichia coli . These plants are traditional medicinal plants of the Chumash American Indians of Southern California. Bioassay-guided fractionation led to the isolation of three flavonoid compounds from A. californica : jaceosidin (1 ), jaceidin (2 ), and chrysoplenol B (3 ). Compounds1 and2 exhibited antibacterial activity against E. coli Δ tolC in liquid cultures. The in vitro activity of1 against the enoyl reductase enzyme (FabI) was measured using a spectrophotometric assay and found to completely inhibit FabI activity at a concentration of 100 μM. However, comparison of minimum inhibitory concentration values for1 –3 against E. coli Δ tolC and an equivalent strain containing a plasmid constitutively expressing fabI did not reveal any selectivity for FabI in vivo . Abstract :